Influence of carbide reinforcements on accumulative roll bonded Al 8011 composites. Issue 8 (11th June 2019) - Chandrasekar, P.; Natarajan, S.; Ramkumar, K. R.
ABSTRACT: Numerous methods are available to produce ultrafine grained material in severe plastic deformation (SPD) techniques. Accumulative roll bonding (ARB) is the most effective techniques to produce ultrafine grained composites with superior properties. The present investigation deals with the fabrication and comparison of Al 8011 composite by introducing various reinforcements such as Titanium carbide (TiC), Tungsten carbide (WC), Boron carbide (B4C) and Zirconium carbide (ZrC) through ARB technique by deforming plastically. Here, four specimens were prepared by incorporating 8 wt.% each of aforementioned carbide particles in Al matrix and compared with each other and characterized through advanced microscopic techniques such as SEM, EDAX, EBSD and TEM besides XRD. Furthermore, Vickers microhardness test and tensile test were conducted. The introduced reinforcement particles were found dispersed evenly throughout the surface by increasing the passes up to eight times. Among these reinforcements, Al 8011 – B4C composite has provided better strength than other composites due to following reasons: (i) high bonding of the interface between the sheets (ii) interlocking of B4C particles within the matrix (iii) higher hardness and strength. Hence, B4C reinforced Al composite claims greater significance for being recommended as an effective alternative for the aluminum material in load carrying applications.